2020
DOI: 10.3390/ani10112182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roughage Quality and Particle Size on Rumen Parameters and Fatty Acid Profiles of Longissimus Dorsi Fat of Lambs Fed Complete Feed

Abstract: The fatty acid composition for the longissimus dorsi (LD) fat of carcass sheep is a crucial factor impacting meat quality. We performed a 90-day feeding trial of 25 Naemi lambs to investigate the effects of roughage sources (alfalfa or wheat straw) of two sizes (regular and 1 cm chopped) when fed with pelleted total mixed ration (TMR) on the growth performance, fermentation patterns, and fatty acid (FA) composition of longissimus dorsi (LD) fat. Lambs were randomly assigned to individual pens with five treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Sheep fat is similar to fat from other ruminants such as cattle. Consistent with our results, the fats in ruminant sediments include mainly saturated and monounsaturated fats, and C16:0, C18:0, and C18:1 c9 account for approximately 80% of the total fatty acids (47). Studies have shown that an increased C18:0 content makes mutton taste heavier (goaty), and the Dongxiang tribute mutton had the lowest C18:0 content (48).…”
Section: Screening Of the Mutton Quality Index To Calculate Comprehen...supporting
confidence: 90%
“…Sheep fat is similar to fat from other ruminants such as cattle. Consistent with our results, the fats in ruminant sediments include mainly saturated and monounsaturated fats, and C16:0, C18:0, and C18:1 c9 account for approximately 80% of the total fatty acids (47). Studies have shown that an increased C18:0 content makes mutton taste heavier (goaty), and the Dongxiang tribute mutton had the lowest C18:0 content (48).…”
Section: Screening Of the Mutton Quality Index To Calculate Comprehen...supporting
confidence: 90%
“…The ADG was 150 gm and the average FCR was 7.71. It means that particle size did not affect total DMI or organic matter (OM) intake in sheep, as reported by previous researchers [16 , 17] .…”
Section: Discussionsupporting
confidence: 74%
“…The FCR of the RCF (6.32) and PCF (7.63) lambs was better than that of feedlot lambs (8.61–9.07), as reported by Saldanha et al [20] . Matar et al [16] reported FCRs of 7.12–8.05 using a pelleted TMR.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid content of meat can be affected by the animal production system [21,22], breed or genotype [23,24], gender [25], age at slaughter [26], liveweight [27], level of fatness [20], type of muscle and feed. In lamb [28], cattle, swine, and poultry [29], it has been suggested that dietary manipulation can be utilized to improve the fatty acid content and nutritional value of meat that more closely meets nutritional guidelines. However, due to extensive rumen microbial biohydrogenation in ruminants, dietary polyunsaturated fatty acids (PUFA) are converted to saturated fatty acids (SFA), absorbed in the small intestine, and deposited in edible tissues (muscles), products (milk), and organs (liver, kidney and heart), thereby causing more health challenges to consumers [30,31].…”
Section: Introductionmentioning
confidence: 99%